The history of public participation in ecological research. Issue 6 (1st August 2012) - Miller-Rushing, Abraham; Primack, Richard; Bonney, Rick
Abstract : Members of the public have for centuries recorded their observations of the natural world, including plant and animal distribution and phenology, water quality, weather data, and astronomical phenomena. Given the relatively recent growth of ecological research as a professional field of study, the historical contributions of amateurs to ecology can be easily overlooked. To better understand long‐term changes in ecosystems, researchers are now revisiting many of these historical datasets collected by non‐professionals. Over the past 100 years, scientific organizations have increasingly included volunteers in large‐scale monitoring projects to broaden the geographical extent and sample size of observations. We believe that a renewed interest in citizen science, enriched with the perspective and data provided by the long tradition of public participation in science, will broaden the engagement of the public in ecological research and lead to new scientific insights.